Neural perspectives on morality due to beguiling mechanisms - Koppang, Haavard; Wenstøp, Søren; Pineda, Jaime A. (Frontiers in Psychology, 2024)
We consider deception an example of behavior that challenges traditional explanations of moral behavior. Beguiling mechanisms, by which we mean deceptiveness with charming seduction for diversion, subtly influence moral sensitivity and judgment in moral dilemma situations. The duality of beguiling mechanisms is important to grasp, including how they relate to the ambiguity of situations. Further, we view moral behavior as quasi-adaptive, affectively based, and reliant on the processes of social cognition, arising out of a set of domain-general primitive predispositions that aggregate to produce moral “mindsets” and increasingly complex moral actions. Building on recent theoretical developments, contend that morality involves a complex heterarchical-hierarchical neurological architecture, where activity is dynamically and contextually dependent, as well as dependent on evolved brain structures and early life year socialization. We contribute to conceptualizing moral behavior from an integrated modern neural perspective. This provides a balance between moral decisions as situational, emotional, and genetically completed non-conscious processes, and the more traditional view of conscious reasoning. Beguiling mechanisms illustrate an integrative model of morality, consistent with emerging insights from affective and cognitive neuroscience.